(3NdGUI GdCTHGgs - (3dejQRG Ydj QVGs
(3ChdgG (B:s
(3GdbSe GdChd(B: (3aef GdbhGYO hGdCUhd GdYGeI aj GdbhGYO GdfMhjI, hgh jTJed Ydi KdGKI hYTQjf MQakG s
(3BNQgG (B:s
(3eHJhQ, hBNQ GdehLhO efgG ef (B"(3HGH LeY GdJcSjQ(B" (3bhdgbGd GHf MjGf(B: (3dG CYde NdGakG aj hLhH aJM GdYjf aj feQhOFd YfO GdfSH s
(3HChdgG cJH CfgG fbdJ ef fSNI GdCUds
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B118 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdfMhs